Early Inflammatory Status Related to Pediatric Obesity - Mărginean, Cristina Oana; Meliţ, Lorena Elena; Ghiga, Dana Valentina; Mărginean, Maria Oana (Frontiers in Pediatrics, 2019)
Background. Obese individuals are in a chronic inflammatory status due to the malfunction of immune-related activities in the adipose tissue, involving a transient infiltration of neutrophils within the abdominal fat and their binding to adipocytes. Neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are considered cost-effective markers for the detection of subclinical inflammation. Our study intended to assess the early stages of inflammation associated to overweight and obesity in children. Material and method. We performed a prospective study with 164 children aged between five and 18 years, admitted to a Pediatric Tertiary Hospital in Romania, between January 2018 and January 2019. The patients were divided according to body mass index (BMI) into two groups: group 1: 77 overweight and obese children (BMI percentile  85), and group 2: 87 children with a normal BMI, in order to evaluate the correlation between BMI and laboratory parameters (CBC, ESR, transaminase, total protein, albumin, and blood glucose levels), inflammatory biomarkers, NLR and PLR, and changes in abdominal ultrasound findings. Results: We found that the leukocyte, lymphocyte, erythrocyte, platelet, CRP and transaminase levels were significantly higher in the overweight/obese group (p=0.0379, p=0.0002, p=0.0003, p=0.0006, p<0.0001, p=0.0332, and p<0.0001, respectively). No significant statistical differences between the two groups in terms of neutrophil, hemoglobin, albumin, total protein, and glycemia levels were noted (p>0.05). Moreover, NLR and PLR did not differ significantly between the two groups (p=0.4674 and p=0.9973, respectively). Conclusions: Obesity is associated with systemic low-grade inflammation reaching alarming rates worldwide among both children and adults. Our study proved that leukocyte, lymphocyte, erythrocyte, and platelet levels are significantly higher in overweight/obese children, emphasizing the inflammatory status related to this condition. Therefore, obesity-related studies involving pediatric patients are of major interest in order to develop appropriate methods to prevent the development of further complications in adulthood.